Sensorimotor Integration in the Whisker System 2015
DOI: 10.1007/978-1-4939-2975-7_10
|View full text |Cite
|
Sign up to set email alerts
|

The Robot Vibrissal System: Understanding Mammalian Sensorimotor Co-ordination Through Biomimetics

Abstract: SummaryWe consider the problem of sensorimotor co-ordination in mammals through the lens of vibrissal touch, and via the methodology of embodied computational neuroscienceÑusing biomimetic robots to synthesize and investigate models of mammalian brain architecture. The chapter focuses on five major brain sub-systems and their likely role in vibrissal system functionÑsuperior colliculus, basal ganglia, somatosensory cortex, cerebellum, and hippocampus. With respect to each of these we demonstrate how embodied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 96 publications
(104 reference statements)
1
9
0
Order By: Relevance
“…A model of the basal ganglia (BG) [4,22] is then used to select, with persistence and pre-emption, one of these plans for execution by the motor plant at any one time. Overall, this system corresponds closely to similar, hardwired, behavior systems that have been identified in several animal species, including rodents [31] and amphibians [14].…”
Section: Brainstemsupporting
confidence: 73%
See 3 more Smart Citations
“…A model of the basal ganglia (BG) [4,22] is then used to select, with persistence and pre-emption, one of these plans for execution by the motor plant at any one time. Overall, this system corresponds closely to similar, hardwired, behavior systems that have been identified in several animal species, including rodents [31] and amphibians [14].…”
Section: Brainstemsupporting
confidence: 73%
“…Any behavioral plan is encoded as an open-loop trajectory for a point in the frame of reference of one of the robotÕs kinematic links. In all current plans, the point chosen corresponds to a Ògeneralized sensory foveaÓ [30,31] just in front of the nose; thus, MIRO is Òled by the noseÓ as a behavioral plan executes. The MPG comprises a kinematic self-model that is computed by moving the guided point and then identifying the remaining parameters (undriven) of the model through a principle of Òleast necessary movementÓ, starting with the most distal DOFs.…”
Section: Brainstemmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in Whiskerbot we looked at early sensory processing in an embodied spiking neuron model of the primary afferent nerve fibers coupled to fiber-glass whiskers instrumented with strain gauges and controlled by shape-memory-alloy artificial muscles. Our research with this model demonstrated to us the importance of fine control of the movement and positioning of the whisker for effective sensing [19] and led us to build additional degrees of freedom for whisker and head positioning into our later robots. As this work has progressed we have also added more elements to the brain-based control architecture.…”
Section: Tactile Sensing In Mammal-like Robotsmentioning
confidence: 97%